PENGETAHUAN IBU DAN DUKUNGAN SUAMI DALAM PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) PADA PASANGAN USIA SUBUR (PUS) - Jumita, Jumita (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
Nearly all cases of cervical cancer (99%) are associated with high-risk human papillomavirus (HPV) infection, a virus that is very commonly transmitted through sexual contact. The aim of the research was to determine the relationship between maternal knowledge and husband's support with VIA examinations at PUS in the Bermani Ulu Community Health Center working area, Rejang Lebong Regency. The type of research design is an analytical survey using a cross sectional design. The population of all PUS in the working area of ​​the Bermani Ulu Community Health Center, Rejang Lebong Regency in March 2023 is 1082 people. Sampling used accidental sampling technique. Data analysis used univariate analysis and bivariate analysis with the Chi-Square statistical test (χ2). Research results from 62 respondents, most respondents (61.3%) had sufficient knowledge, most respondents (54.8%) did not have husband support, most respondents (69.4%) had never carried out an VIA examination in the work area of ​​the Community Health Center Bermani Ulu, Rejang Lebong Regency. There is a relationship between maternal knowledge and IVA examination at PUS in the Bermani Ulu Community Health Center working area, Rejang Lebong Regency with a p-value (0.000). There is a relationship between husband's support and IVA examination at PUS in the Bermani Ulu Community Health Center working area, Rejang Lebong Regency with p-value (0.002). It is hoped that suggestions can increase public knowledge about IVA examinations and the importance of husbands' support in carrying out IVA examinations both through counseling and health education so that PUS awareness of carrying out IVA examinations increases.